(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article provides a bibliographic analysis of libraries in the Kokand Khanate and their impact on the literary environment of Kokand, books in libraries and their. The article also analyzes the information about the Kokand khans who contributed to the development of the library, as well as the fate of the khanate library